A Review on Use of Cloud in Education Sector - Patil, Vishal S; Kale, Pooja; Sawale, Priyanka (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is rising field in computing . it is vast technology enhancing day by day when people are online they can get faster access to their data due to massive storage. It is the way to maximise capacity and capabilities without spending a lot to buy the infrastructure and software cloud computing is also involved in education sector ,because education is highly important in today’s life. In this paper we show hoe cloud computing used in education sector to improve teaching and learning methodology. As education is not just restricted to classroom with student today’s education is heavily depend on information technology. Cloud provide solution for that user use the platform and application on-campus or off-campus or combination of both depending on need. It offer service at least cost. In this paper we proposed architectures for cloud and did comparative analysis to make more secure data over cloud every technology has security threats.